Chemical and molecular bases of dome formation in human colorectal cancer cells mediated by sulphur compounds from Cucumis melo var. conomon. Issue 12 (6th November 2020) - Kamimura, Miyu; Sasaki, Azusa; Watanabe, Shimpei; Tanaka, Shiho; Fukukawa, Akiko; Takeda, Kazuya; Nakamura, Yasushi; Nakamura, Takako; Kuramochi, Kouji; Otani, Yui; Hashimoto, Fumio; Ishimaru, Kanji; et al.
Abstract : Colorectal cancer was the third most commonly diagnosed malignant tumor and the fourth leading cause of cancer deaths worldwide in 2012. A human colorectal cancer cell line, RCM‐1, was established from a colon cancer tissue diagnosed as a well‐differentiated rectum adenocarcinoma. RCM‐1 cells spontaneously form 'domes' (formerly designated 'ducts') resembling villiform structures. Two sulphur‐containing compounds from Cucumis melo var. conomon (Katsura‐uri, or Japanese pickling melon), referred to as 3‐methylthiopropionic acid ethyl ester (MTPE) and methylthioacetic acid ethyl ester (MTAE), can induce the differentiation of the unorganized cell mass of an RCM‐1 human colorectal cancer cell culture into a dome. However, the underlying molecular mechanisms of such dome formation have not been previously reported. Here, we performed a structure–activity relationship analysis, which indicated that methylthioacetic acid (MTA) was the lowest molecular weight compound with the most potent dome‐inducing activity among 37 MTPE and MTAE analogues, and the methylthio group was essential for this activity. According to our microarray analysis, MTA resulted in down‐regulation of 537 genes and up‐regulation of 117 genes. Furthermore, MTA caused down‐regulation of many genes involved in cell‐cycle control, with the cyclin E2 ( CCNE2 ) and cell division cycle 25A ( CDC25A ) genes being the most significantly reduced. Pharmacological analysis showed that the administration of two cell‐cycle inhibitors for inactivating CDC25A phosphatase (NSC95397) and the cyclin E2/cyclin‐dependent kinase 2 complex (purvalanol A) increased the dome number independently of MTA. Altogether, our results indicate that MTA is the minimum unit required to induce dome formation, with the down‐regulation of CDC25A and possibly CCNE2 being important steps in this process. Abstract : This study showed that methylthioacetic acid (MTA), an analogue of the sulphur‐containing phytochemicals isolated from Cucumis melo var. conomon, most potently differentiated RCM‐1 colon cancer cells into domes. MTA was shown to strongly down‐regulate CDC25A and CCNE2, and their inhibitors prompted dome formation independently of MTA, suggesting that MTA may induce dome formation through dysfunction of these G1 regulators.